Microfinance, an alternative to the capital crisis. - Andrade Romero, Mauro; Andrade Merino, Raúl; Tapia Hermida, Ligia (mktDESCUBRE; Vol 1 No 15 (2020): Fifteenth Edition (January - June), 2020)
Poverty, linked to the lack of job opportunities, unemployment, incipient public policies, widespread corruption in public management, political, social, economic scene of uncertainty;   are causes for the search for financial alternatives that will alleviate the economic recession facing Ecuador. The current financial offer in Ecuador does not guarantee assistance to the informal or poorer sector of the Ecuadorian economy to generate resources or employment, however, the popular financial organizations immersed in the credit process do not   become as yet into the solution to the crisis of the capital. The search for resources led the government to go to the multilateral credit agencies to maintain the chain of production, distribution and consumption of products and services. The new debt was destined to overcome budget and investment deficits, and ordinary expenses; and maintain the productive system. Microfinancing can become into a mechanism to keep the primary production sector operating, trying to keep the production and consumption chain constant.